(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2022)
It has become superfluous to talk about the specificity of creative syntax, and this creative peculiarity is manifested in the artistic creative function of language with artistic beauty, and its impactful purpose at the same time; Because every writer is keen to distinguish his language with a special style and special features, so he resorts to linguistic techniques and expressive stylistic paths, which remove him from the usual standard speech, and from these creative paths the sent metaphor; As the writer resorts to relying on it, as a metaphorical contiguous image, working to express one word with another for the reason of association, contextual juxtaposition, and the significance between them. Taking into account the foregoing, the research sought to study selected models of metaphors sent in the sermons of Nahj al-Balaghah, according to some of its relationships, as permitted by the place, in order to discover the stylistic features and the aesthetic secrets inherent in the use of these figurative images in the different contexts in which they were mentioned.